8-Aminoguanine and its actions in the metabolic syndrome - Edwin K. Jackson; Delbert G. Gillespie; Zaichuan Mi; Lori A. Birder; Stevan P. Tofovic (Scientific Reports, 2024)
Abstract The metabolic syndrome is characterized by obesity, insulin resistance, dyslipidemia and hypertension and predisposes to cardiorenal injury. Here, we tested our hypothesis that 8-aminoguanine, an endogenous purine, exerts beneficial effects in Zucker Diabetic-Sprague Dawley (ZDSD) rats, a preclinical model of the metabolic syndrome. ZDSD rats were instrumented for blood pressure radiotelemetry and randomized to vehicle or 8-aminoguanine (10 mg/kg/day, po). The protocol was divided into four phases: Phase 1: 17 days of tap water/normal diet; Phase 2: 30 days of 1% saline/normal diet; Phase 3: 28 days of 1% saline/diabetogenic diet; Phase 4: acute/terminal measurements. 8-Aminoguanine: (1) decreased mean arterial blood pressure (P = 0.0004; 119.5 ± 1.0 (vehicle) versus 116.3 ± 1.0 (treated) mmHg) throughout all three phases of the radiotelemetry study; (2) rebalanced the purine metabolome away from hypoxanthine (pro-inflammatory) and towards inosine (anti-inflammatory); (3) reduced by 71% circulating IL-1β, a cytokine that contributes to hypertension-induced adverse cardiovascular events and type 2 diabetes; (4) attenuated renovascular responses to angiotensin II; (5) improved cardiac and renal histopathology; (6) attenuated diet-induced polydipsia/polyuria; and (7) reduced HbA1c. In the metabolic syndrome, 8-aminoguanine lowers blood pressure, improves diabetes and reduces organ damage, likely by rebalancing the purine metabolome leading to reductions in injurious cytokines such as IL-1β.